2020
DOI: 10.3390/vaccines8030425
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Profile of Type-Specific Human Papillomavirus Infection after Initiation of HPV Vaccination

Abstract: Organized human papillomavirus vaccination (OHPV) in Japan was introduced in 2010 for girls aged 12–16 years who were born in 1994 or later. The rate of OHPV coverage was 70–80%. However, after suspension of the government vaccination recommendation, the coverage dramatically decreased. We aim to investigate the change in prevalence of HPV infection after the initiation of HPV vaccination. We recruited females aged 20–21 years attending public cervical cancer screening from 2014 to 2017 fiscal years (April 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…HPV vaccine is known to exert a cross-protection effect against other types of HPV, except for HPV 16 and 18. 5 , 8 It has been reported that both bivalent and quadrivalent HPV vaccines exert a cross-protection effect against HPV 31, 33, 35, 39, 45, 52, 58, and 59. 5 , 9–12 Thus, in our study, we examined the prevalence of other types of HPV as well.…”
Section: Resultsmentioning
confidence: 99%
“…HPV vaccine is known to exert a cross-protection effect against other types of HPV, except for HPV 16 and 18. 5 , 8 It has been reported that both bivalent and quadrivalent HPV vaccines exert a cross-protection effect against HPV 31, 33, 35, 39, 45, 52, 58, and 59. 5 , 9–12 Thus, in our study, we examined the prevalence of other types of HPV as well.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported a significant preventive effect of the HPV vaccine against HPV 16/18 infection in Japanese women aged 20–22 years 6,7 . We also analyzed the preventive effect against abnormal cytology and histology in women aged 20 years and compared pre‐vaccination cohorts (those born between 1991 and 1993) to those born when public funding became available for the HPV vaccine (born between 1994 and 1996).…”
Section: Introductionmentioning
confidence: 99%
“…5 We previously reported a significant preventive effect of the HPV vaccine against HPV 16/18 infection in Japanese women aged 20-22 years. 6,7 We also analyzed the preventive effect against abnormal cytology and histology in women aged 20 years and compared prevaccination cohorts (those born between 1991 and 1993) to those born when public funding became available for the HPV vaccine (born between 1994 and 1996). We found that the incidence of cytological abnormalities, ASC-US or worse (ASC-US+) decreased by 24%, LSIL or worse (LSIL+) decreased by 73%, and CIN3 decreased significantly from 0.8% to 0% (P = 0.016) in cohorts eligible for publicly funded vaccination.…”
mentioning
confidence: 99%
“…We investigated HPV infection rates in women aged 20-21 years undergoing cervical screening in Niigata City from April 2014 to March 2021 (fiscal years 2014-2020) [6] (supplementary Figure 1). HPV vaccination coverage in the target cohorts increased from 30.8% (2014) to 87.8% (2015), 90.0% (2016) and 92.9% (2017), followed by 89.6% (2018) and 89.2% (2019).…”
mentioning
confidence: 99%